Proses Terbentuknya Teritorialitas pada Permukiman Padat Penghuni di Kampung Jawa, Denpasar - Mentari Indriani, Ni Ketut Ayu Intan Putri (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 5 No 1 (2018): April 2018, 2018)
Territoriality is a pivotal element in the study of architecture. It relates to functions that personify one's spatial behaviour in achieving a desired level of privacy. Territoriality works in parallel with a sense of belonging as well as one's controlling and defensive attitudes toward a supposedly claimed spatial context. In the populated urban settlement of the overly crowded Kampung Jawa of Denpasar City, access to space becomes a privilege its occupants hold dearly. The growing population has consequently escalated its demand for space that has no practical resolution given the amount of land available. In turn, this has affected people's manner in sharing, adapting, and conceiving their space. Grounded by such in such conditions, this study aims at identifying various territorial phenomena that take place in Kampung Ja wa, as well as the spatial and social adaptations associated with each observed territorial setting. The study implements a qualitative approach and explains its findings in a descriptive manner. Primary data was collected through on-site observation and depth interviews conducted by a group of key informants. In summary, the study concludes that given a desired level of privacy, spatial containment has a direct influence on behaviour and encourages flexibility in how space is deployed and functions. Keywords: territoriality, over-populated settlement, Kampung Jawa , Denpasar City